A practical attitude control scheme for hypersonic vehicle based on disturbance observer. (September 2019) - Piao, Minnan; Yang, Zhihong; Sun, Mingwei; Huang, Jian; Chen, Zengqiang
This paper proposes a practical three-channel attitude control scheme for hypersonic vehicle based on the linear active disturbance rejection control. The control scheme considers the weak and strong coupling scenarios separately due to the dynamic characteristics. For the weak coupling case, three linear active disturbance rejection controllers are designed for the Euler angles of the three channels, respectively, to deal with the strong uncertainties. The expected stability margin and dynamic performance can be guaranteed through the stability margin tester tuning method. Moreover, the control scheme for the pitch, yaw, and roll angles can be applied to the control of the angle of attack, the sideslip angle and the bank angle directly according to the flight dynamics of the hypersonic vehicle, thus realizing a unified control framework for all the attitude angles. For the strong coupling scenario like the fast reversal maneuver, the inner-loop angular rate feedback is performed first in this paper to enhance the damping characteristics, and then linear active disturbance rejection control is designed for the augmented plant to eliminate the strong coupling effects. Simulation results demonstrate the satisfactory tracking and disturbance rejection ability of the proposed methods.